ANALISIS PEMBIAYAAN MUDHARABAH, MUSYARAKAH DAN MURABAHAH UNTUK MENINGKATKAN PENDAPATAN PADA PT BANK SYARIAH MANDIRI CABANG MEDAN AKSARA - Nainggolan, Edisahputra (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
The purpose of this study was to determine and analyze the cause of a large Financing income received while small, and to investigate the causes of financing products for the results (profit sharing) channeled smallest of murabahah financing and Musyarakah. Research approaches used descriptive research approaches, data collection techniques used in this study interviews and documentation. Data analysis techniques used in this research is descriptive analysis technique that is by collecting data and classifying data obtained from the company with the existing theory so as to provide a clear picture of the object being studied.Results showed Financing great while revenues received by little it is because of financing problems in the implementation of the payment of financing by the customer that happens things like financing is not smooth, the financing of which the debtor does not meet the requirements that were promised, and these costs are not on schedule installments, troubled financing is one of the definite risks faced by each bank because the risk is often also called credit risk. and financing products for the results (Mudarabah) channeled smallest of Murabahah financing and Musyarakah and this is because of financing is financing with a high degree of risk and should be based on a strong element of trust. And the uncertainty of revenue to be earned as well as concerns about the loss or fraud is becoming the main cause.Keywords: Mudarabah, Musyarakah and Murabahah, Mudarabah Income from Musharakah and Murabahah